Anáforas encapsuladoras: uma análise em textos de opinião - Bertucci, Roberlei Alves (2006)
From the referential progression ideas, discourse objects and referenciality, this paper wants to analyze the occurrence of encapsulators anaphors, known as encapsulations, in the opinion texts. It finds to show some characters of this kind of anaphor and, at the same time, to comprehend what of theses characters are more common in the opinion texts. Besides, the paper presents some expressions with demonstrative pronouns, that are commons in the encapsulations, that are not in the encapsulators anaphors field.